AtSPX1-mediated transcriptional regulation during leaf senescence in Arabidopsis thaliana. (June 2019) - Yan, Hengyu; Sheng, Minghao; Wang, Chunchao; Liu, Yue; Yang, Jiaotong; Liu, Fengxia; Xu, Wenying; Su, Zhen
Highlights: AtSPX1 might function as positive regulator of age-triggered leaf senescence in Arabidopsis thaliana . During leaf ageing, AtSPX1 expression level is dramatically increased, leading to the upregulation of several key senescence-related transcription factors, such as WRKYs and NACs. AtSPX1 plays a key role in the crosstalk among leaf senescence, Pi starvation and SA signal transduction. Abstract: Leaf senescence is the final stage of leaf growth, a highly coordinated and complicated process. Phosphorus as an essential macronutrient for plant growth is remobilized from senescing leaves to other vigorous parts of the plant. In this study, through data mining, we found some phosphate starvation induced genes such as AtSPX1, were significantly induced in aging leaves in Arabidopsis. We applied a reverse genetics approach to investigate the phenotypes of transgenic plants and mutant plants, and the results showed that the overexpression of AtSPX1 accelerated leaf senescence, suppressed Pi accumulation, promoted SA production and H2 O2 levels in leaves, while the mutant lines of AtSPX1 showed slightly delayed leaf senescence. We conducted RNA-seq-based transcriptome analysis together with GO and GSEA enrichment analyses for transgenic vs. wild-type plants to elucidate the possible underlying regulatory mechanism. The 558 genes that were up-regulated in the overexpression plants 35S::AtSPX1/WT, were significantly enriched in the process of leaf senescence, Pi starvation responses and SA signaling pathways, as were the target genes of some transcription factors such as WRKYs and NACs. In a word, we characterized AtSPX1 as a key regulator, which mediated the crosstalks among leaf senescence, Pi starvation and SA signaling pathways in Arabidopsis thaliana .